PEMANFAATAN MEDIA DIGITAL DALAM PEMASARAN KUE TRADISIONAL “WULAN” - Rita Friyani; Novita Ekasari; Nurhayani; Wira Lestari; Rosmeli (JURNAL DAYA-MAS, 2025)
Digital media is a forum on the internet where its users can represent themselves, interact, cooperate, share, communicate with other users, and form social bonds virtually. Digital media has various impacts that affect people's behavior, namely positive and negative impacts. The cake business produces human food products whose ingredients use processed agricultural and livestock products. This business is widely carried out as a micro, small, to medium-scale home business. “Wulan” Traditional Cake is a culinary business that provides traditional cakes, pastries, and wet cakes, such as engkak and masubah. Wulan Traditional Cake only sells offline and has not utilized digital media for product marketing. Community service aims to make it easier for partners to do marketing using social media such as Instagram and support the RESTRA of the University of Jambi and the vision of UNJA to become a World Class Entrepreneurship University. The service that has been carried out includes the achievement of Technology for Digital Transformation goals. The result of this PPM activity is that “Wulan” Traditional Cake utilizes digital media by creating a special Instagram account to sell online and, in the future, collaborates with applications such as grabfood and gofood to sell online.